Heavy metal assessment of groundwater quality in part of Karu, Central Nigeria - Aisha Abubakar Kana (Water Practice and Technology, 2022)
Assessment of groundwater quality remains essential in water management; anthropogenic practices such as industrial and agricultural activities can have negative impacts on groundwater quality. The present study assessed heavy metal contamination of groundwater in Karu, Central Nigeria. Heavy metal was evaluated by the indices: degree of contamination, heavy metal pollution and evaluation. Groundwater was found to be significantly contaminated with heavy metal concentrations exceeding the WHO limit for drinking water, particularly around areas of poultry farming, dumpsite and dimension stone quarry and processing plant. Groundwater is therefore considered unsafe for not only drinking purposes but also poultry. Strong correlation was observed between the degree of contamination and heavy metal evaluation index; between Pb, Fe and all indices; between TDS and Pb; Pb and Fe, Fe and Zn, Zn and Cu, Ni and Cu/Zn. The elements Pb, Zn, Cu, Fe and Ni contribute significantly to the contamination observed relative to the others. Groundwater contamination is attributed to anthropogenic activities within the study area; therefore, waste disposal practices require modification. The study presents a case for environmental (both baseline and impact) assessment and continuous monitoring to control pollution of groundwater. HIGHLIGHTS The first of its kind in the study area.; Provides baseline data on heavy metal load in groundwater of the study area.; Forms background for further analysis.;